THE EXPERIENCES OF PEOPLE WITH DEPRESSION IN THE WORKPLACE IN UZBEKISTAN - Davron Akramov Sadriddinovich (Modern American Journals, 2025)
Objectives. Much research has been done before on the experiences of people suffering from depression in the employment setting in the past. However, most of that research has been conducted in Western countries and few developed Asian countries. No study exploring this topic has been carried out in Uzbekistan. Therefore, the aim of this study was to explore the experiences of people suffering from depression in the workplace in Uzbekistan.
Keywords: workplace, mental health, depression, job performance, organizational behaviour.